Synthesis of aryl α-keto esters via the rearrangement of aryl cyanohydrin carbonate esters - Nopporn Thasana (2018)
A facile synthesis of aryl α-keto esters is reported involving the rearrangement of aryl cyanohydrin carbonate esters induced by the α-carbanion to the nitrile group generated by LDA. However, under similar conditions, an o-benzyloxycyanohydrin carbonate ester rearranged via a domino reaction leading to 2-phenylbenzofuran-3-carboxylic acid. © 2003 Elsevier Science Ltd. All rights reserved.